2014
DOI: 10.3177/jnsv.60.114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrient Composition of Dinner on Sleep Architecture and Energy Metabolism during Sleep

Abstract: Summary Energy metabolism and substrate oxidation during sleep correlate with sleep stage, suggesting that energy metabolism affects sleep architecture or vice versa. The aim of the present study was to examine whether changes in energy metabolism during sleep, induced by a high-carbohydrate or high-fat meal for dinner, affect sleep architecture. Ten healthy males participated in this study, sleeping 3 nonconsecutive nights in a whole-room calorimeter. The first night was scheduled as an adaptation to the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…Although it cannot be confirmed, it has been hypothesized that carbohydrate oxidation also suppresses SWS (21,31), which would support the findings of reciprocal changes in REM and SWS due to carbohydrate manipulation (20,24). It was previously reported that an HC diet reduces growth hormone secretion in men, but not in women, after a 10-d dietary intervention (32).…”
Section: Dietary Patterns and Sleep Qualitysupporting
confidence: 53%
See 3 more Smart Citations
“…Although it cannot be confirmed, it has been hypothesized that carbohydrate oxidation also suppresses SWS (21,31), which would support the findings of reciprocal changes in REM and SWS due to carbohydrate manipulation (20,24). It was previously reported that an HC diet reduces growth hormone secretion in men, but not in women, after a 10-d dietary intervention (32).…”
Section: Dietary Patterns and Sleep Qualitysupporting
confidence: 53%
“…Yajima et al (21) found similar changes in SWS after the consumption of an HC test meal. In a similar fashion, healthy men underwent a 1-d randomized crossover intervention with Numerical data not provided.…”
Section: Dietary Patterns and Sleep Qualitymentioning
confidence: 49%
See 2 more Smart Citations
“…On the other hand, sleep also affects food metabolism in its own term. As an example, carbohydrates decrease the duration of slow wave sleep (18). This is why eating and drinking during long work shifts has led to reduced reaction time and improved performance (19).…”
Section: Introductionmentioning
confidence: 99%